2021
DOI: 10.3389/fcimb.2021.642216
|View full text |Cite
|
Sign up to set email alerts
|

Novel Endosymbionts in Rhizarian Amoebae Imply Universal Infection of Unrelated Free-Living Amoebae by Legionellales

Abstract: Legionellales-infected water is a frequent cause of local outbreaks of Legionnaires’ disease and Pontiac fever. Decontaminations are difficult because Legionellales reproduce in eukaryotic microorganisms (protists). Most often, Legionellales have been isolated from amoebae; however, the culture-based sampling methods are taxonomically biased. Sequencing studies show that amoebae in the cercozoan class Thecofilosea are dominant in soils and wastewater treatment plants, prompting us to screen their capability to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…Most of these findings documented the involvement of amoebozoans and heteroloboseans representative in such interactions (Balczun and Scheid, 2017;Shi et al, 2021). However, recent work has demonstrated that numerous rhizarian FLA could also bear intracellular bacteria, thereby confirming that tight FLA-bacteria interactions indeed occur in all these taxonomic groups (Pohl et al, 2021;Solbach et al, 2021).…”
Section: Rosculus Vilicus Interacts With Map For At Least a Few Daysmentioning
confidence: 92%
“…Most of these findings documented the involvement of amoebozoans and heteroloboseans representative in such interactions (Balczun and Scheid, 2017;Shi et al, 2021). However, recent work has demonstrated that numerous rhizarian FLA could also bear intracellular bacteria, thereby confirming that tight FLA-bacteria interactions indeed occur in all these taxonomic groups (Pohl et al, 2021;Solbach et al, 2021).…”
Section: Rosculus Vilicus Interacts With Map For At Least a Few Daysmentioning
confidence: 92%
“…Cultures were established with Saccharomyces cerevisiae as prey. Cell sorting as described in Solbach et al (2021) or serial manual washings in sterile medium were used to establish cultures free of environmental bacteria.…”
Section: Sampling and Isolationmentioning
confidence: 99%